Determinan Profitabilitas Perbankan Nasional di Indonesia: Determinants of Profitability of National Banking in Indonesia - Hayati, Nur; Musdholifah, Musdholifah (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2014)
This research aims to analyze the effect of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Operating Expenses to Operating Income (BOPO), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM) on the profitability proxy with return on assets (ROA) at commercial banks listed on the Indonesia Stock Exchange from 2005 to 2010. The samples used are 14 commercial banks listed on the Indonesia Stock Exchange. The samples are taken using purposive sampling method with certain criteria. The method used in this study is to use multiple regression analysis to test the hypothesis that the t test and the f test. Before using a multiple regression analysis, performed the classic assumption test first. The results obtain in this study are simultaneously CAR, NPL, BOPO, LDR, and NIM effect on profitability by 44%. While partially CAR, BOPO, and NIM effect on profitability and LDR NPL does not affect profitability.